2021
DOI: 10.21608/aadj.2021.208209
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Evaluation of Oral Health Among Orthodontic Patients Prior Treatment, During Treatment and Post-Treatment

Abstract: Aim: to evaluate oral health status among orthodontic patients: before, during, post treatment completion. Subjects & methods: Twenty-eight patients were selected from Outpatient clinics seeking Orthodontic treatment, Faculty of Dental Medicine, Al-Azhar University, Cairo, Egypt. A self-administrated questionnaire was prepared covering oral hygiene practice, oral hygiene cleaning aids and previous oral prophylaxis. Oral health status of each patient was assessed using: Gingival bleeding index (GBI), Plaque ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…In the present study, the mean plaque values of New group showed slight increase over time without significant differences, as it was found at evidence-based studies that an initial period of one month following braces installment is a challenging period for patients [23,24]. In addition, these results are similar to a recent study that found that there was on significant increase in plaque index after 3 months of orthodontic treatment compared to that before treatment [25].…”
Section: Plaque Scoressupporting
confidence: 90%
“…In the present study, the mean plaque values of New group showed slight increase over time without significant differences, as it was found at evidence-based studies that an initial period of one month following braces installment is a challenging period for patients [23,24]. In addition, these results are similar to a recent study that found that there was on significant increase in plaque index after 3 months of orthodontic treatment compared to that before treatment [25].…”
Section: Plaque Scoressupporting
confidence: 90%